Child Sexual Abuse In Puttalam, Sri Lanka: A Medico-Legal Analysis - Amararatne, R.R.G.S.; Vidanapathirana, M. (My University, 2016)
Attached

Introduction: All cases of child sexual abuse (CSA) are expected to be examined by specialists in Forensic Medicine in Sri Lanka. Further, management should not be confined to medico-legal aspects but ensure the psycho-social management of child and family. Therefore, this study was conducted to identify and describe patterns of abuse and strategies of management of children affected with CSA. Methods: Retrospective descriptive study was conducted on all the victims of child sexual abuse reported to Base Hospital, Puttalam, Sri Lanka over 20 months from Nov-2014 to June-2016. Results: There were 183 children affected and of them, 168 (92%) were girls. Out of incidents occurred at home, 52% were committed by relatives (p=0.000). All abusers were male and none were strangers. Known non-relatives abused 64% of females and almost all male victims (p=0.02). In more than 10 years old female victims, 80% had hymenal tears (p=0.000). One-third of both males and females had anal penetration. Only five (05) had associated physical abuse. Eighty percent were referred to STI and 84% to psychiatrist. Institutional case conference was held in 20%. It was held in 8% of anal and 20% of genital penetrations (p=0.8).Conclusions: Physical abuse was rarely associated with child sexual abuse. Majority of incidents were committed by male relatives. Known non-relatives are the most potential abusers. Girls more than 10 years are the most vulnerable for penetration. None were given STI prophylactic treatment. Mere presence of injuries were not indications for case conference. However, the follow-up reports of psycho-social managements were not available.
Keywords: Child sexual abuse; Crime patterns; Management strategies